2014
DOI: 10.3171/2014.8.spine1445
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of spinal surgical site infection and vancomycin powder

Abstract: Object Surgical site infection (SSI) is a serious and costly complication of spinal surgery. There have been several conflicting reports on the use of intrawound vancomycin powder in decreasing SSI in spine surgery. The purpose of this study is to answer the question: “Does intrawound vancomycin powder reduce the rate of SSIs in spine surgery?” Methods A comprehensive search of multiple electronic databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
95
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(109 citation statements)
references
References 51 publications
(62 reference statements)
4
95
0
10
Order By: Relevance
“…However, we could not find a connection between high postoperative ESR levels and the presence of a SSI. In concordance of our study, it was reported in the literature that CRP was more sensitive and specific than ESR when evaluating the response to the treatment of infection (27)(28)(29).…”
Section: Biochemical and Microbiological Investigationssupporting
confidence: 92%
“…However, we could not find a connection between high postoperative ESR levels and the presence of a SSI. In concordance of our study, it was reported in the literature that CRP was more sensitive and specific than ESR when evaluating the response to the treatment of infection (27)(28)(29).…”
Section: Biochemical and Microbiological Investigationssupporting
confidence: 92%
“…In the USA and UK, about 50% of bacteria detected in infected patients in intensive care units are MRSA 18,[27][28][29] ; i.e., the AMP protocol currently administered intravenously is effective for only about 50% of hospital infection cases. Thus, intrawound vancomycin has recently been clinically applied and its efficacy has been frequently reported 14,19,[30][31][32] , but the effect has also been questioned in some reports 33,34) .…”
Section: Resultsmentioning
confidence: 99%
“…Godil et al showed that the cost of care for one deep spine infection case is over US$33,000 17) . The cost of a 1 g dose of VCM is US$10-44 14,[17][18][19] , with this cost varying depending on the type of insurance.…”
Section: Medical Costs and Cost Of Vcm For Ssimentioning
confidence: 99%
See 2 more Smart Citations